Studi pendahuluan kandungan Vitamin E pada varietas kelapa sawit PPKS - Retno Diah Setiowati; Yurna Yenni; Frisda Rimbun Panjaitan; Sujadi Sujadi; Mahmud Irfan Lubis; Ernayunita Ernayunita (Pusat Penelitian Kelapa Sawit, 2021)
An oil palm variety with high vitamin E has an added value because of its benefit as pharmaceutical and nutraceutical source. The measurement of the vitamin E content in CPO from eight varieties of oil palm is an effort to obtain high vitamin E varieties with the optimum oil yield. The varieties used in this experiment were DxP PPKS 718, DxP PPKS 239, DxP PPKS 540, DxP Yangambi, DxP Lame, DxP Avros, DxP Simalungun, and DxP Langkat, which were planted in a demonstration block, located at Kebun Adolina PTPN IV. The result showed that the average of the vitamin E from 8 varieties ranged from 477.36 ppm up to 582.78 ppm. The DxP Yangambi has the potency to be improved as the candidate of DxP variety with high vitamin E added value due to its highest vitamin E content. On the other hand, the DxP PPKS 540 is appropriate as candidate of ortets for high vitamin E clones regarding the vitamin E content; which is the highest over the whole samples